FACTORS THAT INFLUENCE THE ACCOUNTABILITY OF LOCAL GOVERNMENT FINANCIAL REPORTS WITH GOOD GOVERNANCE AS AN INTERVENING VARIABLE IN THE GOVERNMENT OF DELI SERDANG DISTRICT - Putri Nur Solati; Irna Triannur Lubis; Fhikry Halomoan Siregar (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
This research aims to find out and analyze whether the Government Internal Control System and the Implementation of Government Accounting Standards have an effect on the Accountability of Regional Government Financial Reports through Good government governance in the Deli Serdang Regency Government. Regionally, the Implementation of Government Accounting Standards has no significant effect on the Accountability of Regional Government Financial Reports, the Government Internal Control System has a significant effect on the Accountability of Regional Government Financial Reports through Good government governance, the Implementation of Government Accounting Standards has no significant effect on the Accountability of Regional Government Financial Reports through Good government governance. to the Deli Serdang Regency Government.